Intergenerational earnings mobility among the children of Canadian immigrants - Abdurrahman Aydemir; Wen-Hao Chen; Miles Corak (Institute for the Study of Labor (IZA), 2006)
We analyze the intergenerational income mobility of Canadians born to immigrants using the 2001 Census. A detailed portrait of the Canadian population is offered as are estimates of the degree of generational mobility among the children of immigrants from 70 countries. The degree of persistence as estimated in regression to the mean models is about the same for immigrants as for the entire population, and there is more generational mobility among immigrants in Canada than in the United States. We also use quantile regressions to distinguish between the role of social capital from other constraints limiting mobility and find that these are present and associated with father's education.
Keywords: I30; I32; I38; 330; immigrants; children; generational mobility; Intertemporale Einkommensverteilung; Soziale Mobilität; Kinder; Migranten; Kanada